2011
DOI: 10.5402/2011/808560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ-Irradiation on the Dielectric and Conductivity Properties of Nano-Wollastonite

Abstract: Nanocrystalline porous CaSiO 3 ceramic powders have been synthesized by a novel low-temperature initiated self-propagating, gas-producing solution combustion method. Single phase β-CaSiO 3 (Wollastonite) is formed by calcination at 900• C for 3 h. The crystallization and phase formation temperatures in this method are found to be lower compared to the powder obtained via solid state reaction method. The powder is characterized by powder XRD (X-Ray Diffraction), and crystallite sizes are evaluated using Scherre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
(16 reference statements)
1
13
0
Order By: Relevance
“…3 that, the dielectrical constant decreased sharply with frequency up to 1 kHz and more slowly in the higher frequency region for the control and irradiated dentin. This feature is similar to those observed in β-CaSiO3 powders (Kulkarni et al, 2011). In addition, the dielectrical constant for the irradiated samples was smaller than the control overall frequency range.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…3 that, the dielectrical constant decreased sharply with frequency up to 1 kHz and more slowly in the higher frequency region for the control and irradiated dentin. This feature is similar to those observed in β-CaSiO3 powders (Kulkarni et al, 2011). In addition, the dielectrical constant for the irradiated samples was smaller than the control overall frequency range.…”
Section: Discussionsupporting
confidence: 71%
“…The effect of γ-irradiation on the dielectrical properties and conductivity behavior of nanowollastonite was previously reported (Kulkarni et al, 2011). It was found that, the exposure to γ-radiation results in substantial modification in the properties of the ceramic powder due to changes in the porosity of the material.…”
mentioning
confidence: 95%
“…A higher value of 'n' implies that large energy is stored in such collective motions [19]. The value of n is 0.90 for un-doped sample [9]. With doping, the conductivity is found to increase as the grain resistance dominates over grain boundary resistance, and the value of n increases to 0.92.…”
Section: Conductivity Formalismmentioning
confidence: 72%
“…A normal relaxation was observed in undoped nano CaSiO 3 ceramic prepared by solution combustion method and no relaxation peak was observed in loss tangent plot versus frequency [9]. Thus the electrical microstructure of undoped nano CaSiO 3 is homogeneous and hence its dielectric behaviour does not follow the Maxwell Wagner (MW) relaxation.…”
Section: Dielectric Studiesmentioning
confidence: 82%
See 1 more Smart Citation